Pelatihan Model Kurikulum Situated Game Teaching Through Set Plays Kepada Guru PJOK Di Kecamatan Rangkasbitung Kabupaten Lebak - Widyawan, Dena (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2024)
This workshop activity takes the form of socializing the curriculum model which is based on situated game teaching through set plays to PJOK teachers in collaboration with the Ikatan Guru Olaharaga Nasional (IGORNAS). The training location is at the IGORNAS secretariat, Lebak Regency. This training was attended by PJOK teachers throughout Rangkasbitung District. As a result of this training, PJOK teachers were able to develop content knowledge, follow the five pedagogical steps, and use good classroom management while abandoning conventional learning that they have experienced for years while teaching.